Practical training report: Chief Minister’s Department (CMD) / Rozirosmini Bolhi - Bolhi, Rozirosmini (University Technology MARA Sarawak, 2016)
Chief Minister’s Department (CMD) occupies the Wisma Bapa Malaysia building which is located in Petra Jaya, Kuching, Sarawak. Wisma Bapa Malaysia was completed in 1976 and officiated by the former Chief Minister of Sarawak, Tun Rahman Yaakub. The building has 22 storey and among the highest building built during it's time. Wisma Bapa Malaysia has become a central for administration for the Sarawak State Government and is the Chief Minister’s office until now. The Chief Minister’s Department (CMD) is responsible for the Sarawak Civil Services (PANS) as a whole and is led by the State Secretary who reports directly to the Chief Minister. The State Secretary is assisted by two Deputy State Secretaries. Based on the created vision, Chief Minister’s Department has developed 5 strategic thrusts to guide the action plan which are: • Research, Planning and Development • Human Capital • System and Technology • Creativity and Innovation • Team Synergy and High Performance Chief Minister’s Department comprises of 11 Units in which every Unit is divided into divisions and sections. Among the eleven Units, one of it is State Human Resources Unit (SHRU). With the former name of Human Resource Management Unit, on April 2015, the name has been changed to State Human Resource Unit (SHRU) in which the rebranding is in line with the new vision and mission. The function of the State Human Resource Unit is to act as primary change agent in the management of human resources in Sarawak Civil Service. The State Human Resource Unit is responsible in reviewing and developing policies and procedures of human resource management in order to remain relevant and to ensure consistent implementation across all service levels.